Laser irradiation pretreatment improves endometrial preparation of frozen-thawed embryo transfer in recurrent implantation failure patients. (2nd August 2020) - Tsai, Hsiao-Wen; Wang, Peng-Hui; Hsu, Pei-Te; Chen, San-Nung; Lin, Li-Te; Li, Chia-Jung; Tsui, Kuan-Hao
Abstract: Recurrent implantation failure (RIF) remains a clinical dilemma. Helium-Neon (He-Ne) laser irradiation has recently become more popular under certain clinical conditions. Given the unique therapeutic effects, we were interested in determining whether pretreatment with He-Ne laser irradiation prior to frozen-thawed embryo transfer (FET) would improve the microcirculation and cause the release of growth factors and cytokines, thus improving endometrial receptivity and the clinical pregnancy rates. Patients chose for themselves whether to proceed with ( n  = 29) or without ( n  = 31) pretreatment with He-Ne laser irradiation prior to FET. The clinical pregnancy rate (37.9%) and implantation rate (20.3%) were higher in the laser-treatment group than in the control group (35.5% and 15.9%, respectively, p  = .844 and .518, respectively). The live birth rate was higher in the laser-treatment group (27.6% vs. 25.8%, respectively, p  = .876) and the miscarriage rate was lower in the laser-treatment group (18.2% and 27.3%, respectively, p  = .611). No side effects or complications from laser irradiation were encountered in patients who received the laser treatment. We concluded that pretreatment with He-Ne laser prior to FET may be an alternative choice for RIF-affected women; however, additional well-designed prospective studies are necessary to determine the precise clinical value of this treatment.